First person - Lauren Falkenberg (The Company of Biologists, 2021)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Lauren Falkenberg is first author on ' Ccdc103 promotes myeloid cell proliferation and migration independent of motile cilia', published in DMM. Lauren is a MD/PhD student in the lab of Joshua S. Waxman at Cincinnati Children's Hospital Medical Center, Cincinnati, OH, USA, investigating the intersection of rare disease biology, human genetics and immunology.